A Selective Electrochemical Sensor for the Detection of Cd(II) Based on a Carbon Paste Electrode Impregnated with a Novel Ion‐imprinted Hybrid Polymer. Issue 6 (19th March 2021) - Adauto, Anais; Wong, Ademar; Khan, Sabir; Picasso, Gino; del Pilar Taboada Sotomayor, María
Abstract: An electrochemical sensor (CPE‐IIHP) was developed for Cd(II) using a carbon paste electrode (CPE) impregnated with an ion‐imprinted hybrid polymer (IIHP). A CPE‐NIHP was also prepared for comparison. DPASV was used to optimize the sensor response and quantify Cd(II). The sensor presented a wide linear range from low concentrations of Cd(II): 1 to 100 μg L −1 and high concentrations of Cd(II): 2.75 to 5.0 mg L −1 . Ions such as Co(II), Pb(II), Ni(II), Zn(II), Fe(II), Fe(III), Sn(II) and Cu(II), showed no variation in the Cd(II) signal. The CPE‐IIHP was successfully applied in river and drinking water analysis, revealing the great potential for its application. Abstract :